Enhancing Seismic Performance of Steel-Plated Stress-Ribbon Bridge with Tuned Mass Dampers: A Finite-Element Study - Hua Dong; Yi Zhang; Zhiqiang Huang; Wuchuan Pu; Kaiwen Liu; Qishuo Zhang (Advances in Civil Engineering)
There has been a noticeable rise in the construction of lightweight stress-ribbon pedestrian bridges. In regions with a high risk of seismic activity, it is crucial to employ advanced seismic control technology to mitigate the impact of earthquakes and improve the bridge’s performance and durability. The objective of this study is to investigate the effect of tuned mass dampers (TMDs) on a steel-plated stress-ribbon bridge using the finite element method. The study aims to analyze the performance of various TMD designs focusing on both vertical and torsional modes. Multiple TMD configurations are considered and numerically compared. The results indicate that TMDs offer both a tuning effect and a static mass effect for stress-ribbon bridges. The tuning effect is most pronounced when the mass ratio falls between 2% and 4%. Installing a single TMD with a mass ratio of 0.05 can decrease vertical displacement along the entire span by up to 36%. Furthermore, a torsional TMD effectively reduces both the torsion of stress ribbons and the pier forces. As a recommendation, the combination of a single vertical displacement TMD and a torsional TMD can be considered the most appropriate scheme for earthquake response control. Moreover, the addition of TMDs reduces the bridge’s sensitivity to the direction of earthquake excitation. These findings contribute to a broader understanding of the earthquake performance of stress-ribbon bridges and assist designers in selecting appropriate control schemes to address vibrational issues.